Pemurnian Bioetanol Hasil Fermentasi Kulit Nanas Menggunakan Proses Distilasi - Adsorpsi Pada Variasi Jenis Perlakuan Dan Ukuran Pori Adsorben - Diah Pramushinta; Said Zul Amraini; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One of the alternatives is by utilizing bioethanol as a renewable alternative energy source. This study aims to obtain ethanol from pineapple feel using solid state fermentation process and the purification using distillation and adsorption process, obtain comparative data on the adsorption capacity of the natural zeolite without activation and the activated natural zeolite, to get data the optimum of adsorbent to produce bioethanol, and characterize the physical properties of bioethanol and qualitative test by GC-MS. The pore size of adsorbent variations are 60; 100; 200 mesh and variation of treatment of adsorbent the natural zeolite without activation and the activated natural. From the research is obtained the highest bioethanol concentration average is 10,44 % volume. The most effective process for ethanol purification is distillation and adsorption process by natural zeolite adsorbent without activation with pore size of 200 mesh. Ethanol content increased from 95 % to 99.8 % v. Bioethanol from distillation and adsorption process in accordance with ISO standards. Keywords: Bioethanol; solid state fermentation; zeolite; distillation and adsorption process